Progression to kidney failure in ADPKD: the PROPKD score underestimates the risk assessed by the Mayo imaging classification - Allmer, Daniela Maria; Parada Rodriguez, Diego; Aigner, Christof; Laccone, Franco; Nagel, Mato; Metz-Schimmerl, Sylvia; Sunder-Plassmann, Gere (Frontiers in Medicine, 2024)
Autosomal-dominant polycystic kidney disease (ADPKD) is the most common inherited kidney disease and fourth leading cause for renal replacement therapy worldwide. Disease progression is tightly linked to genotype, however, factors like genetic modifiers and environmental factors are responsible for a high phenotypic variability within- as well as between families. Individual’s risk of progression to kidney failure is assessed using prediction- or risk-assessment tools such as the predicting renal outcomes in ADPKD score (PROPKD score) and the Mayo Imaging Classification (MIC). The PROPKD score encompasses genetic and phenotypic parameters, while the MIC relies on renal imaging, height, and age of patients. Both methods categorize patients into low-risk, intermediate-risk, and high-risk for progression to kidney failure. In this retrospective, cross-sectional study, we calculated the risk of progression to kidney failure in our population and analyzed the agreement between the methods in three separate models with alternating stratification of MIC risk categories. We found a mismatch for risk assessment between the respective risk categories, indicating that the PROPKD score and MIC should not be used interchangeably. Preferably, the MIC should be used as a base for risk assessment and may be enhanced by genotypic and phenotypic information.